CÂT DE EFICIENTĂ ESTE NOUA METODOLOGIE DIDACTICĂ? - USM ADMIN (Moldova State University, 2011)
This article examines statistically if the learning methodology AMLEUL works or not. To estimate the effectiveness of methodology we select a few statistical tests to be compatible for no-Gaussian character of the series of experimental dates obtained from the assessments at the initial and final phases of the pedagogical-scientific experiment.